If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(3x + 5) + -8(3x + 5) = 0 Reorder the terms: 4x(5 + 3x) + -8(3x + 5) = 0 (5 * 4x + 3x * 4x) + -8(3x + 5) = 0 (20x + 12x2) + -8(3x + 5) = 0 Reorder the terms: 20x + 12x2 + -8(5 + 3x) = 0 20x + 12x2 + (5 * -8 + 3x * -8) = 0 20x + 12x2 + (-40 + -24x) = 0 Reorder the terms: -40 + 20x + -24x + 12x2 = 0 Combine like terms: 20x + -24x = -4x -40 + -4x + 12x2 = 0 Solving -40 + -4x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-10 + -1x + 3x2) = 0 Factor a trinomial. 4((-5 + -3x)(2 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-1.666666667, 2}
| 2*2*3*7= | | 7x+5y+11=0 | | 2/3*2/7= | | (4380-3548)/(0.5-0.2)= | | (0.5-0.2)/(4380-3548)=x | | 4xsquared=18+6x | | (0.5-0.2)/(4380-3548) | | 0=-16t^2+3t+50 | | 127/16+113/36= | | 10=5/4x | | y=-1x+10 | | 3/14-1/18 | | (2x^2)/3=6 | | 9(x-5)+39=8x-6 | | 9x-76=5x+4 | | 9(x-8)+11=9x-60 | | 23x-3=19x+10 | | 9(x-3)+2=9x-25 | | f(x)=40x-20 | | 1x+24=5x-2 | | 5+n=21 | | 40x+25=145 | | 1x+11=7x-9 | | -5(3x-22)=2(x-14)-33 | | .5(x-8)=11+8x | | 3x-5x+4=8x-7x+1 | | 11x-8=2x+7 | | 4/7u=-15/16 | | -16x^2+48x= | | .1(X+10)+.7X=17 | | 4+2x=2(-x+4)-32 | | n+40= |